DESIGN, DEVELOPMENT, AND CHARACTERIZATION OF TOPICAL GEL CONTAINING ITRACONAZOLE - ANTIFUNGAL AGENT - K, Pavithra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main purpose of this study was to develop a topical delivery of itraconazole to reduce the dose of the drug, to improve patient compliance, and to avoid the side effects. Itraconazole is a triazole derivative to treat antifungal and antiprotozoal infections. Methods: Topical gel formulations of itraconazole were prepared using Carbopol 940 as a gelling agent with different concentrations. Four different formulations were prepared and evaluated with respect to color, spreadability, viscosity measurement, determination of pH, drug content, in vitro drug release studies, zeta potential studies, and stability studies. Compatibility study was carried out by Fourier-transform infrared (FT-IR) spectral analysis. Results: FT-IR study revealed that there were no significant interaction between the drug and polymers. All the prepared formulations show acceptable physical properties. The drug content and percentage yield were higher for F1 formulation among all formulation F1 shows better drug release. Stability study of best formulation shows that there was no difference in drug content and in vitro drug release studies. Conclusion: From the above observation results that this formulation may be more encouraging topical substitute for the healing of fungal infections in the skin.